Landmark annotation and mandibular lateral deviation analysis of posteroanterior cephalograms using a convolutional neural network - Takeda, Saori (J Dent Sci, 2021)
BACKGROUND/PURPOSE: Facial asymmetry is relatively common in the general population. Here, we propose a fully automated annotation system that supports analysis of mandibular deviation and detection of facial asymmetry in posteroanterior (PA) cephalograms by means of a deep learning-based convolutional neural network (CNN) algorithm. MATERIALS AND METHODS: In this retrospective study, 400 PA cephalograms were collected from the medical records of patients aged 4 years 2 months–80 years 3 months (mean age, 17 years 10 months; 255 female patients and 145 male patients). A deep CNN with two optimizers and a random forest algorithm were trained using 320 PA cephalograms; in these images, four PA landmarks were independently identified and manually annotated by two orthodontists. RESULTS: The CNN algorithms had a high coefficient of determination (R(2)), compared with the random forest algorithm (CNN-stochastic gradient descent, R(2) = 0.715; CNN-Adam, R(2) = 0.700; random forest, R(2) = 0.486). Analysis of the best and worst performances of the algorithms for each landmark demonstrated that the right latero-orbital landmark was most difficult to detect accurately by using the CNN. Based on the annotated landmarks, reference lines were defined using an algorithm coded in Python. The CNN and random forest algorithms exhibited similar accuracy for the distance between the menton and vertical reference line. CONCLUSION: Our findings imply that the proposed deep CNN algorithm for detection of facial asymmetry may enable prompt assessment and reduce the effort involved in orthodontic diagnosis.